The Concentration Equation for Transient Processes in a Gas Centrifuge Based on the Axial Averaging Approach - ZENG Shi (Journal of Isotopes, 2022)
A concentration equation that describes the mass transfer in transient processes is required for analyzing the separation in transient processes of a gas centrifuge. It is desirable that the equation is simple but is able to reflect the characteristics in transient separation processes to avoid heavy numerical computation. A partial differential equation governing the axial distribution of concentrations in a gas centrifuge is derived from the general equation of mass transfer at unsteady state based on the axial averaging approach. By employing the variable density isothermal rigid body model, the equation is further simplified and analyzed. The dispersion mass source/sink introduced as the result of the model is handled during the simplification to make the concentration solvable.